(untitled) (Fiep Bulletin - online, 2015)
The purpose of this paper is to investigate the relation between the development of sports and the role of the sports media. As example we will use the specific case of volleyball. We consider that the changes carried through the last years have had, initially, the potential to attract the general public and consequently ended up attracting the media for its divulgation. The minnonette appeared in 1895 with William Morgan and in 1896 already had its first change in name for the sport that today we know as volleyball. Since then they had been innumerable changes, until the present state of things, which still presents itself propitious for newer changes in its rules. We will use in our research the writings of Elias & Dunning (1992) to consider the questions concerning the development of the sports along the last decades, as well as the works of Parlebas (1998) on the sociology of the sport. For the relation of the sport with the media, we use the studies of Pozzi & Ribeiro (2004). Our research is of a qualitative nature, where we analyze the points-of-view of professionals involved in this sport.